Pressure-sensitive adhesive composite sheet
By controlling the adhesive strength and UV absorption characteristics of the adhesive tape, combined with the composition of specific monomers and functional monomers, the problems of thermal stability and low pollution at high temperatures are solved, and efficient adhesion and low pollution performance are achieved.
Patent Information
- Application Number
- JP2024180329
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-10-16
- Filing Date
- 2024-10-15
- Publication Date
- 2025-04-28
AI Technical Summary
Existing tapes lack thermal stability and low pollution characteristics, especially when used at high temperatures, they are prone to adhesive residues and contamination problems.
By controlling the adhesive strength of the tape on the Cu plate at high temperature, combined with the UV absorption peak below 0.22 abs in the range of 250-300nm and the adhesive stripping rate is less than 2, an adhesive layer consisting of 70-90% soft media, 5-20% specific monomers and functional monomers is used to ensure that the tape maintains good adhesion performance at high temperatures and reduces contamination.
The tape maintains excellent adhesion and low pollution characteristics at high temperatures, avoiding adhesive residues and contamination problems, and improving thermal stability and peeling properties.
Smart Images

Figure 2025068623000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an adhesive composite sheet, and more particularly to an adhesive composite sheet having excellent adhesiveness, heat resistance and low contamination properties. [Background technology]
[0002] Adhesive tapes are widely used because they are known to provide functions such as temporary fixation and heat-resistant protection by being attached to the surfaces of various adherends in various industrial fields. However, conventional adhesive tapes lack heat resistance, and after use at high temperatures, especially when attached to the surface of an adherend and peeled off, the surface of the adherend is prone to contamination due to adhesive residue.
[0003] Therefore, there is a need to develop an adhesive tape that reduces the above-mentioned defects while also having excellent adhesiveness, heat resistance, and low contamination. Summary of the Invention [Problem to be solved by the invention]
[0004] The present invention has been made to solve the above-mentioned conventional problems, and its object is to provide an adhesive composite sheet that not only has excellent adhesiveness and heat resistance, but also has low staining properties and does not cause staining due to adhesive residue on the adherend. [Means for solving the problem]
[0005] As a result of intensive research to solve the above problems, the inventors of the present invention have found that the ultraviolet absorption peak in the wavelength range of 250 to 300 nm of the adhesive composite sheet and the rate of change in peel adhesion F of the adhesive layer against a Cu plate at 180° and a pulling speed of 300 mm / min are A / F B We have found that the above problem can be solved by controlling the adhesive strength of the adhesive sheet attached to the Cu plate to within a specific range, i.e., by controlling the adhesive strength so that there is almost no change before and after high-temperature treatment, and have completed the present invention.
[0006] In other words, the present invention is as follows. [1]. An adhesive layer is included. The ultraviolet absorption peak in the wavelength range of 250 to 300 nm is 0.22 abs or less, The rate of change in peel adhesive strength of the adhesive layer against a Cu plate at 180° and a pulling speed of 300 mm / min F A / F B is less than or equal to 2, However, F A indicates the adhesive strength measured at 23°C after the adhesive layer was attached to a Cu plate and heated at 200°C for 1 hour, F B The adhesive composite sheet shows the adhesive strength measured at 23°C when the adhesive layer was attached to a Cu plate. [2] The adhesive composite sheet according to [1], wherein the surface energy of the adhesive layer at 23° C. is 20 to 30 mN / m. [3] The pressure-sensitive adhesive layer is formed from a pressure-sensitive adhesive composition; The adhesive composition comprises a base polymer, and the base polymer contains, relative to 100 parts by weight of the total monomer components of the base polymer, 70 to 90 parts by weight of a soft monomer, 5 to 20 parts by weight, preferably 5 to 10 parts by weight, of a monomer represented by the following formula (a) or formula (b), and 5 to 12 parts by weight of a functional monomer. The adhesive composite sheet according to [1] or [2]. [ka] (In formula (a), X1 represents -NH-R, where R represents an alkyl group having 1 to 6 carbon atoms, a cycloalkyl group having 3 to 20 carbon atoms, or a heterocyclic group having 3 to 20 carbon atoms; A represents a side chain having one C=C at the end. [ka] (In the formula (b), X2 represents -NH, A represents a side chain having one C=C at the end. [4] The adhesive composite sheet according to [3], wherein the base polymer satisfies any one of the following conditions (i) to (iii): (i) The soft monomer is a (meth)acrylate monomer represented by the following formula (c) and has a glass transition temperature of -80 to -10°C. [ka] (In formula (c), Z represents an alkyl group or a cycloalkyl group having 3 to 20 carbon atoms, Y represents a hydrogen atom or a methyl group. (ii) the monomer represented by formula (a) includes at least one selected from the group consisting of N-isopropylacrylamide, dimethylaminopropylmethacrylamide, N-(hydroxymethyl)methacrylamide, and 2-propenoic acid 2-[[(butylamino)carbonyl]oxy]ethyl; The monomer represented by the formula (b) is 2-propenoic acid [2-(2-oxo-1-imidazolidinyl)ethyl], 2-methyl-2-propenoic acid [2-(2-oxo-1-imidazolidinyl)ethyl], 2-propenoic acid [2-(2-oxo-1-imidazolidinyl)propyl], 2-methyl-2-propenoic acid [2-(2-oxo-1-imidazolidinyl)propyl], 2-propenoic acid [2-(2-oxo-1-imidazolidinyl)butyl], 2-methyl-2-propenoic acid [2-(2-oxo-1-imidazolidinyl)butyl], N-[2-(2-oxoimidazolidin-1-yl) The compound includes at least one selected from the group consisting of 2-methyl-N-[2-(2-oxoimidazolidin-1-yl)ethyl]prop-2-enamide, 2-methyl-N-[2-(2-oxoimidazolidin-1-yl)propyl]prop-2-enamide, 2-methyl-N-[2-(2-oxoimidazolidin-1-yl)propyl]prop-2-enamide, N-[2-(2-oxoimidazolidin-1-yl)butyl]prop-2-enamide and 2-methyl-N-[2-(2-oxoimidazolidin-1-yl)butyl]prop-2-enamide. (iii) the functional monomer comprises a hydroxyl group-containing (meth)acrylate monomer and / or a carboxyl group-containing (meth)acrylate monomer, The hydroxyl group-containing (meth)acrylate monomer includes at least one selected from the group consisting of 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, hydroxyoctyl (meth)acrylate, hydroxydecyl (meth)acrylate, hydroxylauryl (meth)acrylate, and [4-(hydroxymethyl)cyclohexyl]methyl (meth)acrylate; The carboxyl group-containing (meth)acrylate monomer includes at least one selected from the group consisting of (meth)acrylic acid, (iso)butenoic acid, (cis / trans)-2-methyl-2-butenoic acid, isomethyl 2-butenoate, isoethyl 2-butenoate, isopropyl 2-butenoate, isobutyl 2-butenoate, 2-carboxyethyl (meth)acrylate, 2-carboxypropyl (meth)acrylate, 2-carboxybutyl (meth)acrylate, and 2-carboxypentyl (meth)acrylate. [5]. The pressure-sensitive adhesive composition further comprises a crosslinking agent; Preferably, the content of the crosslinking agent is 2 to 20 parts by weight, preferably 2 to 15 parts by weight, based on 100 parts by weight of the base polymer; Preferably, the crosslinking agent includes an amino resin-based crosslinking agent. [6] The adhesive composite sheet according to [1] or [2], which satisfies any one of the following conditions (iv) to (viiii): (iv) The pressure-sensitive adhesive layer has a heat loss of 1.0% or less, preferably 0.6% or less at 200° C. (v) The pressure-sensitive adhesive layer has a gel fraction of 20 to 70% as measured at 23° C. after heating at 150° C. for 2 hours. (vi) The adhesive layer was attached to a Cu plate, and the adhesive strength F was measured after leaving the adhesive layer at 23°C x 50% RH for 0.5 h. B is 0.5 to 3.5N / 20mm, preferably 0.5 to 2N / 20mm. (vii) The adhesive layer was attached to a Cu plate, heated at 200°C for 1 hour, and then left at 23°C x 50% RH for 0.5 hours, after which the adhesive strength F was measured. A is 10N / 20mm or less, preferably 5N / 20mm or less. (viii) After the pressure-sensitive adhesive layer is attached to a Cu plate and peeled off, the Cu plate has a surface energy of 30 to 40 mN / m. (viiii) The rate of change in elastic modulus W when the pressure-sensitive adhesive layer is pressed by 500 nm by a nanoindentation method under conditions of 23° C. and 100 Hz B / W A is 1.1 to 3.5, However, the elastic modulus W A is the elastic modulus of the pressure-sensitive adhesive layer at 23°C, Elastic modulus W B is the elastic modulus at 23°C after the pressure-sensitive adhesive layer is heated at 150°C for 2 hours. [7] The adhesive composite sheet according to [1] or [2], wherein the adhesive layer has a thickness of 2 to 200 μm. [8]. The adhesive layer further includes a base layer disposed on one side of the adhesive layer, The substrate layer comprises a polyethylene oxide film (PO film), a polyimide film (PI film), a polyethylene terephthalate film (PET film), a polypropylene film (PP film), or a polyethylene film (PE film); The adhesive composite sheet according to [1] or [2], wherein the thickness of the base layer is 2 to 50 μm. Effect of the Invention
[0007] The adhesive composite sheet according to the present invention not only has excellent adhesiveness and heat resistance, but also has excellent peelability and workability, and does not cause contamination of the adherend due to adhesive residue. When the adhesive composite sheet is used for heat-resistant protection or a heat-resistant sealing process, the heat resistance is not significantly reduced due to thermal degradation. [Brief description of the drawings]
[0008] [Figure 1]1 is a cross-sectional view illustrating a schematic structure of a pressure-sensitive adhesive sheet according to one embodiment of the present invention. [Diagram 2] FIG. 1 is a schematic diagram for evaluating the permeability of a sealing resin. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] Hereinafter, suitable embodiments of the present invention will be described. Matters necessary for carrying out the present invention other than those specifically mentioned in this specification can be understood by a person skilled in the art based on the teachings on carrying out the invention described in this specification and the common general technical knowledge at the time of filing. The present invention can be carried out based on the contents disclosed in this specification and the common general technical knowledge in this field.
[0010] In addition, in the following drawings, the same reference numerals may be used to denote components / parts that perform the same function, and duplicated descriptions may be omitted or simplified. Furthermore, the embodiments shown in the drawings are schematic in order to clearly explain the present invention, and do not necessarily accurately represent the dimensions or scale of the products that are actually provided.
[0011] <Adhesive composite sheet> The adhesive composite sheet according to the present invention has a base layer and an adhesive layer disposed on one side of the base layer, and has an ultraviolet absorption peak of 0.22 abs or less in the wavelength range of 250 to 300 nm, and a peel adhesive strength change rate F of the adhesive layer against a Cu plate at 180° and a pulling speed of 300 mm / min. A / F B is less than or equal to 2, However, F A indicates the adhesive strength measured at 23°C after the adhesive layer was attached to a Cu plate and heated at 200°C for 1 hour, F B indicates the adhesive strength measured at 23°C when the adhesive layer was attached to a Cu plate.
[0012] Fig. 1 is a cross-sectional view showing a schematic structure of an adhesive sheet according to one embodiment of the present invention. As shown in Fig. 1, the adhesive composite sheet 1 has a base layer 10 and an adhesive layer 20 disposed on one side of the base layer 10, and the adhesive layer 20 is preferably disposed over the entire surface of the base layer 10.
[0013] Although not shown, the adhesive composite sheet according to the present invention may have a release liner disposed on the outside of the adhesive layer for the purpose of protecting the adhesive surface until it is supplied for use.
[0014] The concept of the adhesive composite sheet in this specification may include parts called adhesive sheets, adhesive tapes, adhesive labels, adhesive films, etc. The adhesive composite sheets disclosed herein may be in the form of sheets, or may be in the form of adhesive sheets processed into various shapes. In some preferred embodiments, the adhesive composite sheet according to the present invention may be provided in a long shape.
[0015] The adhesive composite sheet according to the present invention has the following characteristics. The adhesive composite sheet has an ultraviolet absorption peak of 0.22 abs or less in the wavelength region of 250 to 300 nm. When the ultraviolet absorption peak in the wavelength region of 250 to 300 nm is within the above range, a crosslinking reaction occurs between the monomer represented by formula (a) or formula (b) and the functional monomer to generate a crosslinking group, increasing the cohesive force, and the adhesive composite sheet has excellent adhesion and heat resistance, and does not cause contamination of the adherend due to adhesive residue.
[0016] The ultraviolet absorption peak in the wavelength region of 250 to 300 nm can be measured, for example, by the method described in the Examples section below.
[0017] The rate of change in peel adhesive strength of the adhesive layer against a Cu plate at 180° and a pulling speed of 300 mm / min F A / F B is 2 or less, but F A indicates the adhesive strength measured at 23°C after the adhesive layer was attached to a Cu plate and heated at 200°C for 1 hour, and FB indicates the adhesive strength measured at 23°C when the adhesive layer was attached to a Cu plate.
[0018] In some preferred embodiments, the rate of change F of the peel adhesion strength of the pressure-sensitive adhesive layer against a Cu plate at 180° and a pulling speed of 300 mm / min is A / F B is preferably 1.9 or less, more preferably 1.8 or less, even more preferably 1.7 or less, and even more preferably 1.6 or less.
[0019] In some preferred embodiments, the rate of change F of the peel adhesion strength of the pressure-sensitive adhesive layer against a Cu plate at 180° and a pulling speed of 300 mm / min is A / F B is preferably 1 or more.
[0020] The adhesive strength can be measured, for example, by the method described in the Examples below.
[0021] The surface energy of the adhesive layer at 23°C and the rate of change in peel adhesion to a Cu plate at 180° and a pulling speed of 300 mm / min F A / F B When both are within the above ranges, the adhesive composite sheet has both excellent adhesiveness and heat resistance, does not cause contamination of the adherend due to adhesive residue, and has excellent releasability and workability.
[0022] If the rate of change in peel adhesive strength is too large, the adhesive composite sheet will be prone to bursting when peeled off, and contamination will easily occur due to breakage or residual adhesive layer on the surface of the adherend. If the rate of change in peel adhesive strength is too small, the adhesive composite sheet will be prone to warping and peeling, and the shielding and protective effect will be lost.
[0023] In some preferred embodiments, the surface energy of the pressure-sensitive adhesive layer at 23°C is 20 to 30 mN / m, with the lower limit being preferably 21 mN / m, more preferably 22 mN / m, even more preferably 23 mN / m, still more preferably 24 mN / m, and the upper limit being preferably 29.5 mN / m, more preferably 29 mN / m, even more preferably 28.5 mN / m, and still more preferably 28 mN / m.
[0024] If the surface energy is not within the above range, the pressure-sensitive adhesive layer may contaminate the surface of the adherend.
[0025] The surface energy can be measured, for example, by the method described in the Examples below.
[0026] [Adhesive layer] The pressure-sensitive adhesive layer according to the present invention includes a base polymer. The pressure-sensitive adhesive layer in the technology disclosed herein may be a layer formed from a pressure-sensitive adhesive composition including a base polymer. The form of the pressure-sensitive adhesive composition is not particularly limited, and may be, for example, a water-dispersed type, a solvent-based type, a hot melt type, an active energy ray curable type (e.g., a photocurable type), or other pressure-sensitive adhesive composition in various forms.
[0027] Each component of the pressure-sensitive adhesive composition according to the present invention will be described in detail below.
[0028] (Base polymer) The pressure-sensitive adhesive composition according to the present invention contains a base polymer. The base polymer may include, for example, an acrylic polymer, a rubber polymer, a polyester polymer, a urethane polymer, a polyether polymer, a silicone polymer, a polyamide polymer, a fluorine-based polymer, etc. Preferably, the pressure-sensitive adhesive composition contains an acrylic polymer as the base polymer.
[0029] The content of the base polymer is not particularly limited, but from the viewpoint of obtaining sufficient adhesive reliability, it is preferably 70% by mass or more, more preferably 80% by mass or more, and even more preferably 90% by mass or more, based on the total amount of the adhesive composition (total mass 100% by mass). By adjusting the content of the base polymer in the adhesive composition to the above range, it is possible to provide an adhesive composition that is excellent in stress relaxation properties and durability, and has excellent adhesiveness to an adherend.
[0030] The base polymer in the technology disclosed herein is preferably a polymer containing the following monomer components: Relative to 100 parts by weight of the total monomer components of the base polymer, the base polymer contains 70 to 90 parts by weight of a soft monomer, 5 to 20 parts by weight, preferably 5 to 10 parts by weight, of a monomer represented by the following formula (a) or (b), and 5 to 12 parts by weight of a functional monomer. [ka] In formula (a), X1 represents -NH-R, where R represents an alkyl group having 1 to 6 carbon atoms, a cycloalkyl group having 3 to 20 carbon atoms, or a heterocyclic group having 3 to 20 carbon atoms; A represents a side chain having one C=C at the end group, [ka] In formula (b), X2 represents -NH; A represents a side chain having one C=C at the terminal group.
[0031] In one preferred embodiment, the soft monomer comprises an alkyl (meth)acrylate. As used herein, the term "alkyl (meth)acrylate" refers to an alkyl acrylate and / or an alkyl methacrylate.
[0032] The (meth)acrylic acid alkyl ester is preferably a (meth)acrylic acid alkyl ester in which the alkyl group has a carbon number of 3 to 20. Specific examples of the (meth)acrylic acid alkyl ester in which the alkyl group has a carbon number of 3 to 20 include, but are not particularly limited to, propyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, pentyl (meth)acrylate, isopentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, butyl ... Examples of the acrylate include isooctyl acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, octadecyl (meth)acrylate, nanodecyl (meth)acrylate, and eicosyl (meth)acrylate. Among these, n-butyl acrylate (BA) and 2-ethylhexyl acrylate (2-EHA) are preferred. The (meth)acrylic acid alkyl esters can be used alone or in combination of two or more.
[0033] In some preferred embodiments, the soft monomer is preferably a (meth)acrylate monomer represented by the following formula (c) and having a glass transition temperature of -80 to -10°C. [ka] (In formula (c), Z represents an alkyl group or a cycloalkyl group having 3 to 20 carbon atoms, Y represents a hydrogen atom or a methyl group.
[0034] Examples of the alkyl group having 3 to 20 carbon atoms, represented by Z, include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a sec-butyl group, a tert-butyl group, an n-pentyl group, an isopentyl group, an n-hexyl group, a 2-ethylhexyl group, a heptyl group, an octyl group, an isooctyl group, a nonyl group, a decyl group, an undecyl group, a dodecyl group, a tridecyl group, a tetradecyl group, a pentadecyl group, a hexadecyl group, a heptadecyl group, an octadecyl group, a nanodecyl group, and an eicosyl group.
[0035] Examples of the cycloalkyl group having 3 to 20 carbon atoms represented by Z include a cyclopropyl group, a cyclobutyl group, a cyclopentyl group, a cyclohexyl group, a cycloheptyl group, a cyclooctyl group, a cyclodecyl group, a cyclododecyl group, a 4-methylcyclohexyl group, and a 4-ethylcyclohexyl group.
[0036] Examples of the (meth)acrylate monomer represented by formula (c) and having a glass transition temperature of -80 to -10°C include 2-ethylhexyl acrylate (Tg: -70°C) and n-butyl acrylate (Tg: -55°C).
[0037] The content of the soft monomer is preferably 70 to 90 parts by mass, more preferably 75 to 89 parts by mass, based on 100 parts by weight of the total monomer components of the acrylic polymer. In some specific embodiments, the content of the soft monomer is preferably 70 parts by mass, 75 parts by mass, 80 parts by mass, 85 parts by mass, or 90 parts by mass, based on 100 parts by weight of the total monomer components of the acrylic polymer. When the content of the soft monomer is within the above range, excellent adhesion can be obtained.
[0038] In the monomer represented by formula (a), X1 represents -NH-R, where R represents an alkyl group having 1 to 6 carbon atoms, a cycloalkyl group having 3 to 20 carbon atoms, or a heterocyclic group having 3 to 20 carbon atoms.
[0039] Examples of the alkyl group having 1 to 6 carbon atoms represented by R include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a sec-butyl group, a tert-butyl group, an n-pentyl group, an isopentyl group, and a hexyl group.
[0040] Examples of the cycloalkyl group having 3 to 20 carbon atoms represented by R include a cyclopropyl group, a cyclobutyl group, a cyclopentyl group, a cyclohexyl group, a cycloheptyl group, a cyclooctyl group, a cyclodecyl group, a cyclododecyl group, a 4-methylcyclohexyl group, and a 4-ethylcyclohexyl group.
[0041] The heteroatom in the heterocyclic group having 3 to 20 carbon atoms represented by R is preferably selected from N, O and / or S. In the present invention, the number of heteroatoms may be 1 or more. Examples of the heterocyclic group having 3 to 20 carbon atoms represented by R include a propiolactone group, a lactam group, a maleic anhydride group, a tetrahydrofuran group, a furyl group, a thienyl group, a pyrrolyl group, a thiazolyl group, a pyridyl group, a pyrimidyl group, a quinolyl group, an indolyl group, and a purinyl group.
[0042] In some preferred embodiments, the monomer represented by formula (a) is preferably a monomer represented by formula (a1): [ka] In formula (a1), Ra1 represents a hydrogen atom or a methyl group, Ra2 represents an alkyl group having 1 to 6 carbon atoms or -Ra4-Ra5, Ra3 represents an alkyl group having 1 to 6 carbon atoms or a hydrogen atom, Ra4 represents an alkylene group having 1 to 6 carbon atoms, and Ra5 represents [ka] or a hydroxyl group, Ra6 represents an alkyl group having 1 to 6 carbon atoms, and Ra7 represents an alkyl group having 1 to 6 carbon atoms.
[0043] Examples of the alkyl group having 1 to 6 carbon atoms represented by Ra2 to Ra4 and Ra6 to Ra7 include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a sec-butyl group, a tert-butyl group, an n-pentyl group, an isopentyl group, and a hexyl group.
[0044] In some preferred embodiments, the monomer represented by formula (a) is preferably a monomer represented by formula (a2) below. [ka] In the formula (a2), Ra8 represents an alkylene group having 1 to 6 carbon atoms, and Ra9 represents an alkyl group having 1 to 6 carbon atoms.
[0045] Examples of the alkylene group having 1 to 6 carbon atoms represented by Ra8 include a methylene group, an ethylene group, a propylene group, a butylene group, a pentylene group, and a hexylene group.
[0046] Examples of the alkyl group having 1 to 6 carbon atoms represented by Ra9 include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a sec-butyl group, a tert-butyl group, an n-pentyl group, an isopentyl group, and a hexyl group.
[0047] In some preferred embodiments, the monomer represented by formula (a) comprises at least one selected from the group consisting of N-isopropylacrylamide, dimethylaminopropylmethacrylamide, N-(hydroxymethyl)methacrylamide, and 2-[[(butylamino)carbonyl]oxy]ethyl 2-propenoate.
[0048] As the monomer represented by the above formula (b), preferred are 2-propenoic acid [2-(2-oxo-1-imidazolidinyl)ethyl], 2-methyl-2-propenoic acid [2-(2-oxo-1-imidazolidinyl)ethyl], 2-propenoic acid [2-(2-oxo-1-imidazolidinyl)propyl], 2-methyl-2-propenoic acid [2-(2-oxo-1-imidazolidinyl)propyl], 2-propenoic acid [2-(2-oxo-1-imidazolidinyl)butyl], 2-methyl-2-propenoic acid [2-(2-oxo-1-imidazolidinyl)butyl], N-[2-(2-oxoimidazolidine-1 The compound includes at least one selected from the group consisting of 2-methyl-N-[2-(2-oxoimidazolidin-1-yl)ethyl]prop-2-enamide, N-[2-(2-oxoimidazolidin-1-yl)propyl]prop-2-enamide, 2-methyl-N-[2-(2-oxoimidazolidin-1-yl)propyl]prop-2-enamide, N-[2-(2-oxoimidazolidin-1-yl)butyl]prop-2-enamide and 2-methyl-N-[2-(2-oxoimidazolidin-1-yl)butyl]prop-2-enamide.
[0049] The content of the monomer represented by formula (a) or (b) is preferably 5 to 20 parts by mass, more preferably 5 to 10 parts by mass, based on 100 parts by weight of the total monomer components of the acrylic polymer. In some specific embodiments, the content of the monomer represented by formula (a) or (b) is preferably 5 parts by mass, 6 parts by mass, 7 parts by mass, 8 parts by mass, 9 parts by mass, 10 parts by mass, 11 parts by mass, 12 parts by mass, 13 parts by mass, 14 parts by mass, 15 parts by mass, 16 parts by mass, 17 parts by mass, 18 parts by mass, 19 parts by mass, or 20 parts by mass, based on 100 parts by weight of the total monomer components of the acrylic polymer. When the content of the monomer represented by formula (a) or (b) is within the above range, the high-temperature self-polymerization properties of the acrylic polymer can be improved, and therefore excellent heat resistance can be obtained.
[0050] As the functional monomer, a monomer having a polar group can be appropriately used. The monomer having a polar group is useful for introducing a crosslinking point into the base polymer or for increasing the cohesive force of the base polymer. The functional monomer may be used alone or in combination of two or more kinds.
[0051] Non-limiting examples of functional monomers include hydroxyl group-containing monomers and / or carboxyl group-containing monomers.
[0052] The content of the functional monomer is preferably 5 to 12 parts by mass, more preferably 6 to 11 parts by mass, relative to 100 parts by mass of all monomer components of the acrylic polymer. When the content of the functional monomer is within the above range, the cohesive force of the pressure-sensitive adhesive can be prevented from becoming too high, and the adhesiveness can be improved.
[0053] The hydroxyl group-containing monomer refers to a monomer having at least one hydroxyl group in the molecule. When the monomer component for constituting the acrylic polymer contains a hydroxyl group-containing monomer, that is, when the acrylic polymer contains a monomer unit derived from a hydroxyl group-containing monomer, a secondary bond such as a hydrogen bond with the adherend is formed, so that the cohesive strength of the acrylic polymer is increased, the change in adhesive strength over time can be more effectively suppressed, and the adhesive residue on the adherend after peeling is less, resulting in higher cohesiveness. The acrylic polymer of this embodiment may use one type of hydroxyl group-containing monomer, or may use two or more types of hydroxyl group-containing monomers.
[0054] As the hydroxyl group-containing monomer, a hydroxyl group-containing (meth)acrylate monomer is preferred.
[0055] Specific examples of hydroxyl group-containing monomers include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, hydroxyoctyl (meth)acrylate, hydroxydecyl (meth)acrylate, hydroxylauryl (meth)acrylate, and [4-(hydroxymethyl)cyclohexyl]methyl (meth)acrylate.
[0056] The content of the hydroxyl group-containing monomer is not particularly limited, but for example, the content of the hydroxyl group-containing monomer is 0.5 to 6 parts by mass, preferably 0.5 to 5 parts by mass, relative to 100 parts by mass of the total monomer components of the acrylic polymer. When the content of the hydroxyl group-containing monomer is within the above range, secondary bonds such as hydrogen bonds with the adherend are formed, so that the cohesive strength of the acrylic polymer is increased, the change in adhesive strength over time can be more effectively suppressed, and less adhesive remains on the adherend after peeling, resulting in higher cohesiveness.
[0057] A carboxyl group-containing monomer refers to a monomer that has at least one carboxyl group in the molecule. By including a carboxyl group-containing monomer in the raw material monomer of an acrylic polymer, secondary bonds such as hydrogen bonds are formed with the adherend, which increases the cohesive strength of the acrylic polymer, more effectively suppresses changes in adhesive strength over time, and leaves less adhesive residue on the adherend after peeling, resulting in higher cohesiveness.
[0058] The carboxyl group-containing monomer is preferably a carboxyl group-containing (meth)acrylate monomer.
[0059] Specific examples of the carboxyl group-containing monomer include (meth)acrylic acid, (iso)butenoic acid, (cis / trans)-2-methyl-2-butenoic acid, isomethyl 2-butenoate, isoethyl 2-butenoate, isopropyl 2-butenoate, isobutyl 2-butenoate, 2-carboxyethyl (meth)acrylate, 2-carboxypropyl (meth)acrylate, 2-carboxybutyl (meth)acrylate, and 2-carboxypentyl (meth)acrylate. Any one of the above carboxyl group-containing monomers may be used alone, or two or more of them may be used in combination.
[0060] The content of the carboxyl group-containing monomer is not particularly limited, but for example, the content of the carboxyl group-containing monomer is preferably 1 to 10 parts by mass relative to 100 parts by mass of the total monomer components of the acrylic polymer. When the content of the carboxyl group-containing monomer is within the above range, secondary bonds such as hydrogen bonds with the adherend are formed, so that the cohesive strength of the acrylic polymer is increased, the change in adhesive strength over time can be more effectively suppressed, and less adhesive remains on the adherend after peeling, resulting in higher cohesiveness.
[0061] The method for obtaining the acrylic polymer is not particularly limited, but various known polymerization methods such as solution polymerization, emulsion polymerization, bulk polymerization, suspension polymerization, and photopolymerization can be appropriately adopted. For example, the solution polymerization method can be preferably adopted. As a method for supplying monomers when carrying out solution polymerization, a batch injection method in which all monomer raw materials are supplied at once, a continuous supply (dropping) method, a divided supply (dropping) method, and the like can be appropriately adopted. The polymerization temperature when carrying out solution polymerization can be appropriately selected depending on the type of monomer and solvent used, the type of polymerization initiator, and the like, and can be set to, for example, about 20 to 170°C (typically about 40 to 140°C).
[0062] The solvent (polymerization solvent) used in the solution polymerization can be appropriately selected from conventionally known organic solvents. For example, any one or a mixture of two or more selected from aromatic compounds (typically aromatic hydrocarbons) such as toluene, acetate esters such as ethyl acetate, aliphatic or alicyclic hydrocarbons such as hexane and cyclohexane, halogenated alkanes such as 1,2-dichloroethane, lower alcohols (e.g. monoalcohols having 1 to 4 carbon atoms) such as isopropyl alcohol, ethers such as tert-butyl methyl ether, and ketones such as methyl ethyl ketone can be used.
[0063] The initiator used in the polymerization can be appropriately selected from conventionally known polymerization initiators according to the type of polymerization method. For example, one or more azo-based polymerization initiators such as 2,2'-azobisisobutyronitrile (AIBN) can be preferably used. Other examples of the polymerization initiator include persulfates such as potassium persulfate; peroxide-based initiators such as benzoyl peroxide and hydrogen peroxide; substituted ethane-based initiators such as phenyl-substituted ethane; and aromatic carbonyl compounds. Further examples of the polymerization initiator include redox-based initiators obtained by combining peroxides with reducing agents. Such polymerization initiators can be used alone or in combination of two or more. The amount of the polymerization initiator used may be a normal amount, and can be selected, for example, from the range of about 0.005 parts by mass to about 1 part by mass (typically about 0.01 parts by mass to about 1 part by mass) relative to 100 parts by mass of the total monomer components.
[0064] The weight average molecular weight (Mw) of the base polymer (preferably an acrylic polymer) in the technology disclosed herein is not particularly limited, but may be, for example, 1,000,000 or less, and is preferably 400,000 or more. Usually, when the weight average molecular weight Mw exceeds 1,000,000, the cohesive force increases due to the effect of entanglement of the polymer, and the fluidity tends to decrease, and a sufficient adhesive area cannot be obtained, so that the adherend cannot be fixed.
[0065] Here, the weight average molecular weight (Mw) refers to a standard polystyrene equivalent value obtained by gel permeation chromatography (GPC). For example, a GPC device with the model name "HLC-8320GPC" (column: TSKgelGMH-H(S), manufactured by Tosoh Corporation) can be used.
[0066] (Crosslinking agent) In the present invention, the pressure-sensitive adhesive composition preferably contains a crosslinking agent in order to adjust the cohesive strength and the like.
[0067] The crosslinking agent preferably contains an amino resin-based crosslinking agent, etc. By using this crosslinking agent, an appropriate crosslinking reaction occurs, which sufficiently improves the cohesive force, ensures good adhesion, and effectively prevents the occurrence of adhesive residue during peeling.
[0068] Examples of amino resin-based crosslinking agents include butyl-etherified melamine-formaldehyde resin, benzoguanamine, methyl-etherified methylol urea, methyl-etherified methylol N,N-ethylene urea, methyl-etherified methylol dicyandiamide, methyl-etherified methylol melamine, methyl-etherified methylol benzoguanamine, butyl-etherified methylol melamine, and butyl-etherified methylol benzoguanamine.
[0069] In the present invention, in addition to the amino resin-based crosslinking agent, the crosslinking agent may further include a crosslinking agent such as an isocyanate-based crosslinking agent or an epoxy-based crosslinking agent.
[0070] The amount of the crosslinking agent used is preferably 2 to 20 parts by mass, more preferably 2 to 15 parts by weight, per 100 parts by mass of the base polymer. By setting the amount of the crosslinking agent used within the above range, the cohesive strength of the adhesive can be increased, the occurrence of adhesive residue on the adherend can be prevented, and the heat resistance of the adhesive composite sheet can be increased. In some embodiments, from the viewpoint of avoiding a decrease in viscosity due to an excessive increase in cohesive strength, the amount of the crosslinking agent used per 100 parts by mass of the base polymer is more preferably 13 parts by mass or less, and even more preferably 12 parts by mass or less.
[0071] In order to carry out the crosslinking reaction more effectively, a crosslinking catalyst may be used. For example, a tin catalyst (e.g., dioctyltin dilaurate) can be preferably used as the crosslinking catalyst. The amount of the crosslinking catalyst used is not particularly limited, but is preferably 0.0001 to 1 part by mass with respect to 100 parts by mass of the base polymer.
[0072] In addition to the above components, the pressure-sensitive adhesive composition according to the present invention may contain various additives, as necessary, that are common in the field of pressure-sensitive adhesives, such as photoinitiators, plasticizers, softeners, antioxidants, antioxidants, etc. As for such various additives, conventionally known additives can be used in the usual manner, provided that the effects of the present invention are not impaired.
[0073] (Formation of adhesive layer) The adhesive layer disclosed herein can be formed by a conventionally known method. For example, a method (direct method) can be adopted in which an adhesive composition is directly applied (typically coated) to the base layer and dried to form an adhesive layer. In addition, a method (transfer method) can be adopted in which an adhesive composition is applied to a surface (release surface) having releasability, dried to form an adhesive layer on this surface, and the adhesive layer is transferred to a base layer. From the viewpoint of productivity, the transfer method is preferred. As the release surface, the surface of a release liner or the back surface of a base layer that has been subjected to a release treatment can be used. The adhesive layer disclosed herein is typically formed continuously, but is not limited to such a form, and may be an adhesive layer formed in a regular or random pattern such as a dotted or striped pattern. The pressure-sensitive adhesive composition can be applied using a conventionally known coater such as a gravure roll coater, a die coater, a bar coater, etc. Alternatively, the pressure-sensitive adhesive composition can be applied by an impregnation method or a curtain coating method.
[0074] The pressure-sensitive adhesive composition is preferably dried by heating from the viewpoints of promoting the crosslinking reaction, improving production efficiency, etc. The drying temperature can be set, for example, at about 40 to 150° C., and is usually preferably set at about 60 to 130° C. After drying the pressure-sensitive adhesive composition, it may be further aged for the purposes of regulating the movement of components in the pressure-sensitive adhesive layer, advancing the crosslinking reaction, relaxing distortion that may exist in the base layer or the pressure-sensitive adhesive layer, etc.
[0075] The thickness of the adhesive layer is not particularly limited, but considering the balance between adhesion to the adherend and cohesiveness, the thickness of the adhesive layer is preferably 2 to 200 μm. By setting the thickness of the adhesive layer within the above range, good adhesion and high temperature resistance can be achieved.
[0076] (Characteristics of adhesive layer) The pressure-sensitive adhesive layer according to the present invention has the following characteristics.
[0077] In some preferred embodiments, the pressure-sensitive adhesive layer has a weight loss upon heating of 1.0% or less, preferably 0.6% or less, when the temperature is increased from 40° C. to 200° C. at a heating rate of 10° C. / min.
[0078] When the heat weight loss rate of the pressure-sensitive adhesive layer is within the above range, a pressure-sensitive adhesive composite sheet having better heat resistance can be provided. When this pressure-sensitive adhesive composite sheet is used in a heat-resistant protection or heat-resistant sealing process, the heat resistance is not significantly reduced due to thermal degradation, and the cohesive force is not reduced.
[0079] The heat loss can be measured, for example, by the method described in the Examples section below.
[0080] In some preferred embodiments, the gel fraction measured at 23° C. after heating the pressure-sensitive adhesive layer at 150° C. for 2 hours is 20 to 70%. When the gel fraction is within the above range, excellent adhesive properties are obtained. The gel fraction can be adjusted, for example, by selecting the composition and molecular weight of the acrylic polymer, the presence or absence of the use of a crosslinking agent, and the type and amount of the crosslinking agent.
[0081] The gel fraction can be measured, for example, by the method described in the Examples section below.
[0082] In some preferred embodiments, the adhesive layer is attached to a Cu plate, and the adhesive strength F is measured after leaving the plate at 23° C. and 50% RH for 0.5 h. B is 0.5 to 3.5N / 20mm, preferably 0.5 to 2N / 20mm.
[0083] Adhesive force F B When the adhesive strength F is within the above range, excellent adhesiveness can be achieved. B If the adhesive strength is less than 0.5N / 20mm, the adhesive composite sheet is likely to peel off due to insufficient adhesive strength. B If the adhesive strength exceeds 3.5 N / 20 mm, the adhesive is difficult to peel off from the adherend, peeling workability is poor, and adverse effects such as contamination due to adhesive residue are likely to occur. The above adhesive strength can be measured, for example, by the method described in the Examples below.
[0084] In some preferred embodiments, the adhesive layer is attached to a Cu plate, heated at 200° C. for 1 h, and then left at 23° C.×50% RH for 0.5 h, after which the adhesive strength F A is 10N / 20mm or less, preferably 5N / 20mm or less.
[0085] When the adhesive sheet has an adhesive strength within the above range after heating at 220°C for 15 minutes, it can maintain excellent adhesive performance, and realize excellent adhesive reliability after aging, as well as excellent peelability and workability. Adhesive Strength F A If the adhesive strength F exceeds 10N / 20mm, the adhesive strength to the adherend increases, peeling workability becomes poor, the adherend is easily damaged during peeling, and contamination due to adhesive residue after peeling is easily caused. A can be measured, for example, by the method described in the Examples below.
[0086] In some preferred embodiments, after the pressure-sensitive adhesive layer is attached to a Cu plate and peeled off, the surface energy of the Cu plate is 30 to 40 mN / m. When the surface energy is in the above range, a low-contamination pressure-sensitive adhesive composite sheet can be provided.
[0087] The surface energy can be measured, for example, by the method described in the Examples below. In some preferred embodiments, the change in elastic modulus W when the pressure-sensitive adhesive layer is indented by 500 nm at 23° C. and 100 Hz by nanoindentation method is B / W A is 1.1 to 3.5. However, the elastic modulus W A is the elastic modulus of the pressure-sensitive adhesive layer at 23°C, Elastic modulus W B is the elastic modulus at 23°C after the pressure-sensitive adhesive layer is heated at 150°C for 2 hours.
[0088] In the present invention, the rate of change in elastic modulus indicates that the pressure-sensitive adhesive layer undergoes secondary crosslinking at high temperatures. When the rate of change in elastic modulus is within the above range, the cohesive force of the pressure-sensitive adhesive layer increases, improving heat resistance, reducing the adhesive residue that occurs when peeling off from the surface of the adherend, and reducing contamination.
[0089] The elastic modulus can be measured, for example, by the method described in the Examples below.
[0090] [Base material layer] The material constituting the base layer of the adhesive composite sheet disclosed herein is not particularly limited, and can be appropriately selected depending on the purpose and manner of use of the adhesive composite sheet.
[0091] As the substrate layer, various film substrates can be preferably used. As the resin material constituting the resin film, for example, polyester, polyolefin (PO), polyamide (PA) such as nylon 6, nylon 66, partially aromatic polyamide, polyimide (PI), polyamideimide (PAI), polyetheretherketone (PEEK), polyethersulfone (PES), polyphenylene sulfide (PPS), polycarbonate (PC), thermoplastic polyurethane (TPU), ethylene-vinyl acetate copolymer (EVA), fluororesin such as polytetrafluoroethylene (PTFE), acrylic resin, polyacrylate, polystyrene, polyvinyl chloride (PVC), polyvinylidene chloride, non-oriented polypropylene (CPP), etc. can be used. The above-mentioned resin film may be a film formed using a resin material containing one kind of such resin alone, or may be a film formed using a resin material in which two or more kinds are blended. The above-mentioned resin film may be a non-oriented film, or may be a film that has been stretched (for example, uniaxially or biaxially stretched). Among these, in order to better realize the effects of the present invention, it is preferable that the base layer contains a polyethylene oxide film (PO film), a polyimide film (PI film), a polyethylene terephthalate film (PET film), a polypropylene film (PP film) or a polyethylene film (PE film).
[0092] The method for producing the resin film is not particularly limited, and any of the conventionally known general resin film forming methods such as extrusion molding, blow molding, T-die casting, and rolling may be appropriately used. The surface of the substrate layer of the present invention may be subjected to any surface treatment in order to improve adhesion to adjacent layers, retention, etc. Examples of the surface treatment include chemical or physical treatments such as chromate treatment, ozone exposure, flame exposure, high-voltage shock exposure, and ionizing radiation treatment, and coating treatment.
[0093] The thickness of the base layer of the present invention is preferably 2 to 50 μm depending on the desired strength, flexibility, purpose of use, and the like.
[0094] (Method of manufacturing adhesive composite sheet) The adhesive composite sheet according to the present invention can be produced by any suitable method, such as a method of applying an adhesive composition to a base layer, or a method of applying an adhesive composition to any suitable substrate to form a coating layer and then transferring the coating layer to the base layer.
[0095] Any suitable coating method can be adopted as the coating method of the pressure-sensitive adhesive composition. For example, each layer can be formed by drying after coating. Examples of the coating method include coating methods using a multi-coater, die coater, gravure coater, applicator, or bar coater, air knife coating, reverse roll coating, kiss coating, dip coating, offset printing, flexographic printing, and silk screen printing. Examples of the drying method include natural drying and heat drying. The heating temperature in the case of heat drying can be set to any suitable temperature depending on the characteristics of the material to be dried.
[0096] (Application) The adhesive composite sheets disclosed herein can be used, for example, in heat-resistant protection or heat-resistant sealing processes, and can provide excellent heat resistance and low contamination. EXAMPLES
[0097] The present invention will be specifically described below using examples, but the present invention is not limited to these examples. The evaluation methods in the examples are as follows. In the examples, "parts" and "%" are based on mass unless otherwise specified. Examples for which no specific conditions are given are performed under normal conditions or conditions recommended by the manufacturer. Materials and equipment used can be commercially available normal products unless otherwise specified.
[0098] <Production of acrylic polymer>
[0099] Manufacturing Example 1 A reaction vessel equipped with a stirrer, a thermometer, a nitrogen inlet tube and a reflux condenser was charged with 89 parts of 2-ethylhexyl acrylate (2-EHA), 2 parts of 2-hydroxyethyl acrylate (HEA), 4 parts of acrylic acid (AA), 5 parts of 2-methyl-2-propenoic acid [2-(2-oxo-1-imidazolidinyl)ethyl] (WAMX), and 200 parts of ethyl acetate as a polymerization solvent. The mixture was stirred at 65°C under a nitrogen atmosphere for 1.5 hours, after which 0.3 parts of 2,2'-azobisisobutyronitrile (AIBN) was added as a polymerization initiator and reacted at 65°C for 4 to 5 hours to obtain a solution of acrylic polymer A1.
[0100] Manufacturing Examples 2 to 6 Acrylic polymers A2 to A6 were produced in the same manner as for acrylic polymer A1, except that the types and amounts of monomer components used were changed as shown in Table 1.
[0101] Comparative Manufacturing Examples 1-4 Acrylic polymers C1 to C4 were produced in the same manner as for acrylic polymer A1, except that the types and amounts of monomer components used were changed as shown in Table 2.
[0102] [Table 1]
[0103] [Table 2]
[0104] <Preparation of adhesive composite sheet>
[0105] Example 1 To the solution of the acrylic polymer A1 produced in the above Production Example 1, 2 parts of butyl etherified melamine-formaldehyde resin (manufactured by BSAF) was added as a crosslinking agent per 100 parts of the acrylic polymer A1 contained in the solution, and the mixture was mixed uniformly to produce a pressure-sensitive adhesive composition B1.
[0106] The adhesive composition B1 was applied to one side of a PI film having a thickness of 25 μm as a base layer, and then heated at 120° C. for 3 minutes to form an adhesive layer having a thickness of 8 μm. A PET release film was then attached to this adhesive layer.
[0107] The evaluation results are shown in Table 3.
[0108] Example 2 To the solution of acrylic polymer A2 produced in Production Example 2 above, 2 parts of benzoguanamine (manufactured by Cytec) as a crosslinking agent was added per 100 parts of acrylic polymer A2 contained in the solution, and the mixture was mixed uniformly to produce adhesive composition B2.
[0109] The adhesive composition B2 was applied to one side of a PI film having a thickness of 25 μm as a base layer, and then heated at 120° C. for 3 minutes to form an adhesive layer having a thickness of 8 μm. In this way, an adhesive composite sheet was obtained.
[0110] The evaluation results are shown in Table 3.
[0111] Examples 3 to 6 An adhesive composite sheet was obtained in the same manner as in Example 2, except that the type of acrylic polymer and the type and amount of crosslinking agent were changed as shown in Table 3. The evaluation results are shown in Table 3.
[0112] Comparative Examples 1 to 4 An adhesive composite sheet was obtained in the same manner as in Example 2, except that the type of acrylic polymer and the type and amount of crosslinking agent were changed as shown in Table 4. The evaluation results are shown in Table 4.
[0113] Comparative Example 5 Silica gel TRA6034C (manufactured by Nitto Denko (Shanghai Matsue) Co., Ltd.) was applied to one side of a PI film having a thickness of 25 μm as a substrate layer to form an adhesive layer having a thickness of 8 μm. In this way, an adhesive composite sheet was obtained. The evaluation results are shown in Table 4.
[0114] [Table 3]
[0115] [Table 4]
[0116] <Evaluation test>
[0117] (1) Surface energy of adhesive layer at 23°C The test fluid was distilled water. Measurement device: KRUSS contact angle meter model DSA100 Specifically, the acrylic polymer was uniformly applied to a SUS403BA plate to a coating thickness of 8 μm, and then dried for 3 minutes at 120° C. In a measurement environment of 23° C. and 50% RH, the measurement sample plate prepared above was placed on the measurement stage of a contact angle meter, and a test liquid was dropped onto the polymer surface to measure the surface energy.
[0118] (2) Adhesive force F B (Adhesive layer attached to Cu plate, adhesive strength measured at 23℃) The adhesive composite sheets produced in each of the Examples and Comparative Examples were used as test sheets. In a standard environment of 23°C and 50% RH, the release liner covering the adhesive surface of each test sheet was peeled off, and the exposed adhesive surface was pressed against an adherend (Cu plate) by rolling a 2 kg roll back and forth once. The test sheet thus pressed against the adherend was left for 30 minutes in the above-mentioned standard environment, and then peeled at a tensile speed of 300 mm / min and a peel angle of 180° in accordance with JIS Z0237 using a tensile tester (manufactured by Shimadzu Corporation, product name "Tensilon"), and the force required for this peeling (180° peel adhesive force) (N / 20 mm) was measured.
[0119] (3) Adhesive force F A (Adhesive layer was attached to a Cu plate, heated at 200℃ for 1 hour, and then the adhesive strength was measured at 23℃.) The adhesive composite sheets produced in each of the Examples and Comparative Examples were used as test sheets. In a standard environment of 23°C and 50% RH, the release liner covering the adhesive surface of each test sheet was peeled off, and the exposed adhesive surface was pressed against an adherend (Cu plate) by rolling a 2 kg roll back and forth once, and then heated in an oven at 200°C for 1 hour. The test sheet thus pressed against the adherend was then left for 30 minutes in the above-mentioned standard environment, after which it was peeled off at a tensile speed of 300 mm / min and a peel angle of 180° in accordance with JIS Z 0237 using a tensile testing machine (manufactured by Shimadzu Corporation, product name "Tensilon"), and the force required for this peeling (180° peel adhesion force) (N / 20 mm) was measured.
[0120] (4) Peak of ultraviolet absorption peak (peak of ultraviolet absorption peak of adhesive composite sheet in the wavelength range of 250 to 300 nm) Sample treatment: 1 g of sample (adhesive layer of adhesive composite sheet produced in each Example and Comparative Example) was immersed in 30 mL of alcohol for 36 hours, and the mixture of alcohol and exudate was measured under the following conditions. Measurement equipment: UV-Visible spectrophotometer, model number U-3900, manufacturer HITACHI Measurement mode: Wavelength scanning Data mode:Abs Starting wavelength: 800.00 nm End wavelength: 190.00 nm Scanning speed: 300 nm / min Sampling interval: 1.00 nm
[0121] (5) Heat loss (heat loss of adhesive layer at 200°C) Measurement equipment: Waters Corporation, Thermogravimetric analyzer model: TGA550; Measurement conditions: Under a nitrogen atmosphere, the temperature was raised from 23°C to 200°C at a heating rate of 10°C / min, and the heat loss at 200°C was measured. Heating rate 10°C / min; constant temperature 240.0 min; mass flow rate 200mL / min.
[0122] (6) Gel fraction (gel fraction measured at 23°C after heating the adhesive layer at 150°C for 2 hours) The naturally dried adhesive layer was heated in an oven at 150°C for 2h, and a sample weighing (0.5-1.0g) m1 was placed in a 50mL glass bottle and immersed in toluene for 1 week. After filtering the immersion mixture with filter paper (product name: NTF-1122), the remaining residue was dried at 120°C and weighed to be m2. Gel fraction = (m1-m2) / m1*100%
[0123] (7) Surface energy of adherend Cu (surface energy of Cu plate after adhesive layer is attached to Cu plate and peeled off) The test fluid was distilled water. Measurement device: KRUSS contact angle meter model DSA100 Specifically, in a standard environment of 23°C and 50% RH, the release liner covering the adhesive surface of each test sheet (adhesive composite sheet produced in each Example and Comparative Example) was peeled off, and the exposed adhesive surface was pressed against the adherend (Cu plate) by rolling a 2 kg roll back and forth once, and then heated in an oven at 200°C for 1 hour, and the test sheet pressed against the adherend in this manner was left for 30 minutes in the above standard environment, and then peeled off at a tensile speed of 300 mm / min and a peel angle of 180° using a tensile tester (manufactured by Shimadzu Corporation, product name "Tensilon") in accordance with JIS Z 0237. The peeled Cu plate was placed on a contact angle meter measurement stage with the peeled surface facing up, and a test liquid was slowly dropped onto the surface of the Cu plate to measure the surface energy.
[0124] (8) Elastic modulus A nanoindentation test was carried out on the surface of the pressure-sensitive adhesive layer under the following conditions using a nanoindenter (product name "TriboIndenter", manufactured by HYSITRON Inc.). Indenter: Berkovich (triangular pyramid) Measurement method: Single indentation measurement Measurement temperature: 23℃ Frequency: 100Hz Indentation depth setting: 500 nm Load: 1mN Load speed: 0.1mN / s Unloading speed: 0.1mN / s Holding time: 1s Specifically, in a measurement environment of 23°C and 50% RH, the release layer of the adhesive layer of the adhesive composite sheet was peeled off, and then the sheet was placed on the nanoindenter measurement stage with the adhesive layer facing the measurement area, and measured under the above measurement conditions.
[0125] (9) Pollution The pressure-sensitive adhesive sheets produced in each of the Examples and Comparative Examples were used as test sheets. In a standard environment of 23°C and 50% RH, the release liner covering the adhesive surface of each test sheet was peeled off, and a 2 kg roll was rolled back and forth once to press the exposed adhesive surface onto the adherend C26000 copper plate, followed by heating in an oven at 200°C for 1 hour. The test sheet thus pressed onto the adherend was then left for 30 minutes in the above standard environment, after which it was peeled off in accordance with JIS Z 0237 using a tensile testing machine (manufactured by Shimadzu Corporation, product name "Tensilon") at a tensile speed of 300 mm / min and a peel angle of 180°, and the adhesive residue on the adherend was observed. ○: No glue residue. △: The area of adhesive residue is greater than 0 and less than 10%. ×: Glue residue area is 10% or more.
[0126] (10) Printability The pressure-sensitive adhesive sheets produced in each of the Examples and Comparative Examples were used as test sheets. In a standard environment of 23°C and 50%RH, the release liner covering the adhesive surface of each test sheet was peeled off, and a 2 kg roll was moved back and forth once to press the exposed adhesive surface onto a C26000 copper plate as an adherend, followed by heating in an oven at 200°C for 1 hour. The test sheet thus pressed onto the adherend was then left for 30 minutes in the above-mentioned standard environment, and then the adhesive sheet on the copper plate was peeled off at a tensile speed of 300 mm / min and a peel angle of 180° in accordance with JIS Z 0237 using a tensile tester (manufactured by Shimadzu Corporation, product name "Tensilon") . 0.5 g of white standard ink was taken out using a doctor blade and applied to the copper plate after peeling, with the thickness of the applied ink set to 0.2 μm ± 0.05, and left to stand for 3 minutes, and the contraction area of the ink was observed. ○: Shrinkage area is less than 5%. △: Shrinkage area is 5-20%. ×: The shrinkage area is more than 20%.
[0127] (11) Permeability of sealing resin The pressure-sensitive adhesive sheets produced in each of the Examples and Comparative Examples were used as test sheets. In a standard environment of 23°C and 50% RH, the liner covering each test sheet was peeled off, and the exposed adhesive surface was pressed against a measurement template (C26000 copper plate 5.5cm long x 5.5cm wide x 0.1mm thick, hollow 0.5cm x 0.5cm square) by rolling it back and forth once with a 2kg roll, and then left for 30min. The side with the adhesive composite sheet attached was placed down on a horizontal heating plate, and epoxy resin (product name "HC-300B6", manufactured by Nitto Denko) was applied to the other side of the measurement template using a doctor blade, with the thickness of the application being 0.5 to 1.0mm. The measurement template treated as above was heated at 175°C for 90s, cooled to 23°C, and the state of resin leakage on the side with the adhesive composite sheet attached was observed in conjunction with Figure 2. ○: No resin leak △: Resin leaks were found in 1 or 2 hollows. ×: Resin leaks were found in 3 to 16 cavities.
[0128] (12) Overall rating Based on the above evaluation results, an overall evaluation was made according to the following criteria. ○: All evaluation items are “○”. △: There are no "X"s in the evaluation items, but there is at least one "△". ×: There is one or more “×” in the evaluation item.
[0129] As can be seen from Table 3, the adhesive composite sheets of Examples 1 to 6 were evaluated as excellent in terms of contamination resistance, printability (ink), and sealing resin permeability. The adhesive composite sheets have excellent high temperature resistance and do not cause contamination of the adherend due to adhesive residue, and can be effectively used in heat-resistant fields such as heat-resistant protection and heat-resistant sealing processes.
[0130] As shown in Table 4, the adhesive composite sheets of Comparative Examples 1 to 5 received poor evaluation results in at least one of contamination resistance, printability (ink), and sealing resin permeability, and therefore cannot be used in heat-resistant fields such as heat-resistant protection and heat-resistant sealing processes. [Industrial Applicability]
[0131] The adhesive composite sheet of the present invention not only has excellent adhesiveness and heat resistance, but also does not cause contamination of the adherend due to adhesive residue, and has excellent peelability and workability, and can be effectively used in fields that utilize heat resistance, such as heat-resistant protection and heat-resistant sealing processes. [Explanation of symbols]
[0132] 1. Adhesive composite sheet 10 Base material layer 20 Adhesive layer
Claims
1. An adhesive layer is included, The ultraviolet absorption peak in the wavelength range of 250 to 300 nm is 0.22 abs or less, The rate of change F of the peel adhesive strength of the adhesive layer against a Cu plate at 180° and a pulling speed of 300 mm / min A / F B is less than or equal to 2, However, F A indicates the adhesive strength measured at 23°C after the adhesive layer was attached to a Cu plate and heated at 200°C for 1 hour, F B The adhesive composite sheet is characterized in that the adhesive layer is attached to a Cu plate and the adhesive strength is measured at 23°C.
2. 2. The adhesive composite sheet according to claim 1, wherein the surface energy of the adhesive layer at 23° C. is 20 to 30 mN / m.
3. The pressure-sensitive adhesive layer is formed from a pressure-sensitive adhesive composition, The adhesive composition comprises a base polymer, and the base polymer comprises, relative to 100 parts by weight of the total monomer components of the base polymer, 70 to 90 parts by weight of a soft monomer, 5 to 20 parts by weight, preferably 5 to 10 parts by weight of a monomer represented by the following formula (a) or (b), and 5 to 12 parts by weight of a functional monomer. The adhesive composite sheet according to claim 1 or 2, characterized in that 【Chemistry 1】 (In formula (a), X 1 represents -NH-R, where R represents an alkyl group having 1 to 6 carbon atoms, a cycloalkyl group having 3 to 20 carbon atoms, or a heterocyclic group having 3 to 20 carbon atoms; A represents a side chain having one C=C at the end. 【Chemistry 2】 (In formula (b), X 2 represents -NH, A represents a side chain having one C=C at the end.
4. The adhesive composite sheet according to claim 3, characterized in that the base polymer satisfies any one of the following conditions (i) to (iii). (i) The soft monomer is a (meth)acrylate monomer represented by the following formula (c) and has a glass transition temperature of -80 to -10°C. 【Chemistry 3】 In formula (c), Z represents an alkyl group or a cycloalkyl group having 3 to 20 carbon atoms; Y represents a hydrogen atom or a methyl group. (ii) the monomer represented by formula (a) includes at least one selected from the group consisting of N-isopropylacrylamide, dimethylaminopropylmethacrylamide, N-(hydroxymethyl)methacrylamide, and 2-propenoic acid 2-[[(butylamino)carbonyl]oxy]ethyl; The monomer represented by the formula (b) is 2-propenoic acid [2-(2-oxo-1-imidazolidinyl)ethyl], 2-methyl-2-propenoic acid [2-(2-oxo-1-imidazolidinyl)ethyl], 2-propenoic acid [2-(2-oxo-1-imidazolidinyl)propyl], 2-methyl-2-propenoic acid [2-(2-oxo-1-imidazolidinyl)propyl], 2-propenoic acid [2-(2-oxo-1-imidazolidinyl)butyl], 2-methyl-2-propenoic acid [2-(2-oxo-1-imidazolidinyl)butyl], N-[2-(2-oxoimidazolidin-1-yl) The compound includes at least one selected from the group consisting of 2-methyl-N-[2-(2-oxoimidazolidin-1-yl)ethyl]prop-2-enamide, N-[2-(2-oxoimidazolidin-1-yl)propyl]prop-2-enamide, 2-methyl-N-[2-(2-oxoimidazolidin-1-yl)propyl]prop-2-enamide, N-[2-(2-oxoimidazolidin-1-yl)butyl]prop-2-enamide and 2-methyl-N-[2-(2-oxoimidazolidin-1-yl)butyl]prop-2-enamide. (iii) the functional monomer includes a hydroxyl group-containing (meth)acrylate monomer and / or a carboxyl group-containing (meth)acrylate monomer, The hydroxyl group-containing (meth)acrylate monomer includes at least one selected from the group consisting of 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, hydroxyoctyl (meth)acrylate, hydroxydecyl (meth)acrylate, hydroxylauryl (meth)acrylate, and [4-(hydroxymethyl)cyclohexyl]methyl (meth)acrylate; The carboxyl group-containing (meth)acrylate monomer includes at least one selected from the group consisting of (meth)acrylic acid, (iso)butenoic acid, (cis / trans)-2-methyl-2-butenoic acid, isomethyl 2-butenoate, isoethyl 2-butenoate, isopropyl 2-butenoate, isobutyl 2-butenoate, 2-carboxyethyl (meth)acrylate, 2-carboxypropyl (meth)acrylate, 2-carboxybutyl (meth)acrylate, and 2-carboxypentyl (meth)acrylate.
5. The pressure-sensitive adhesive composition further comprises a crosslinking agent, Preferably, the content of the crosslinking agent is 2 to 20 parts by weight, preferably 2 to 15 parts by weight, based on 100 parts by weight of the base polymer; The adhesive composite sheet according to claim 3, wherein the crosslinking agent preferably includes an amino resin-based crosslinking agent.
6. The adhesive composite sheet according to claim 1 or 2, characterized in that the adhesive composite sheet satisfies any one of the following conditions (iv) to (viiii). (iv) The pressure-sensitive adhesive layer has a heat loss of 1.0% or less, preferably 0.6% or less at 200° C. (v) The pressure-sensitive adhesive layer has a gel fraction of 20 to 70% when measured at 23° C. after heating at 150° C. for 2 hours. (vi) The adhesive layer was attached to a Cu plate, and the adhesive strength F was measured after leaving the adhesive layer at 23° C.×50% RH for 0.5 h. B is 0.5 to 3.5 N / 20 mm, preferably 0.5 to 2 N / 20 mm. (vii) The adhesive layer was attached to a Cu plate, heated at 200° C. for 1 h, and then left at 23° C. x 50% RH for 0.5 h, after which the adhesive strength F was measured. A is 10N / 20mm or less, preferably 5N / 20mm or less. (viii) After the pressure-sensitive adhesive layer is attached to a Cu plate and peeled off, the Cu plate has a surface energy of 30 to 40 mN / m. (viii) The rate of change in elastic modulus W when the pressure-sensitive adhesive layer is indented by 500 nm at 23° C. and 100 Hz by a nanoindentation method B / W A is 1.1 to 3.5, Where, the elastic modulus W A is the elastic modulus of the pressure-sensitive adhesive layer at 23°C, Elastic modulus W B is the elastic modulus at 23° C. after the pressure-sensitive adhesive layer is heated at 150° C. for 2 hours.
7. 3. The adhesive composite sheet according to claim 1, wherein the thickness of the adhesive layer is 2 to 200 μm.
8. Further comprising a base layer disposed on one side of the pressure-sensitive adhesive layer, The substrate layer includes a polyethylene oxide film (PO film), a polyimide film (PI film), a polyethylene terephthalate film (PET film), a polypropylene film (PP film), or a polyethylene film (PE film), The adhesive composite sheet according to claim 1 or 2, wherein the thickness of the base layer is 2 to 50 μm.